High-resolution dynamics of hemodilution after exercise-related hemoconcentration - Komka, Z.; Szilágyi, B.; Molnár, D.; Sipos, B.; Tóth, M.; Elek, J.; Szász, M. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Hemoconcentration during acute intense exercise is intensively investigated, while the rearrangement of hematological parameters during the recovery period is less understood. The aim of our study was to understand the mechanisms of hemodilution after short-term dynamic exercise.